Reliability model of MMC considering periodic preventive maintenance - Wang,B; Wang,X; Bei,Z; Judge,P; Wang,X; Green,TC (IEEE Transactions on Power Delivery, 2016)
Abstract:Periodic preventive maintenance (PPM) is a significant measure to ensure reliable operation of the modular multilevel converter (MMC), but to date has always been neglected in the reliability evaluation. A mathematical reliability model of MMC considering PPM is proposed in this paper. The model is derived rigorously by the reliability function and finally described by the indices equivalent failure rate and the forced outage rate. Two operation modes related to redundant submodules are considered and described by the standby model and k-out-of-n model, respectively. Employing this model, we can analyze the sensitivity of reliability to redundancy and maintenance interval and provide some reliability indices for planning, which is especially valuable for the offshore cases. The necessity of the considered PPM and the effectiveness of the proposed model are verified by case studies. A method to include PPM in reliability modeling is provided.